Effect of Excitation Migration and Upconversion in Highly Erbium-doped Glass Micro-sphere Lasers - Hoi, Pham Van; Huy, Bui; Chi, Do Thuy (Communications in Physics, 2012)
Excitation migration and upconversion process in the Erbium-doped silica-alumina glass microsphere lasers with concentrations of 2500-4000~ppm were investigated in detail. The experiment shows that under 976~nm excitation, the intense of up-conversion emission at 523, 546 and 657~nm, corresponding to the transitions $^{2}$H$_{11 / 2 } → ^{4}$I$_{15 / }$, $^{4}$S$_{3 / 2} → ^{4}$I$_{15 / 2}$, and $^{4}$F$_{9 / 2} → ^{4}$I$_{15 / 2}$, respectively, $^{ }$depends on the erbium content, migration of excitation and pump power. The excitation migration has strongly influenced on the threshold and Red shift of lasing wavelength and migration-assisted up-conversion process leads to degraded amplification performance of microsphere lasers made by silica-alumina glasses with different contents of Er-ions.